Arterial aging and arterial disease: interplay between central hemodynamics, cardiac work, and organ flow—implications for CKD and cardiovascular disease - London, Gerard (Nature Publishing Group, 2011)
Cardiovascular disease is an important cause of morbidity and mortality in patients with chronic kidney disease (CKD) and end-stage renal disease (ESRD). All epidemiological studies have clearly shown that accelerated arterial and cardiac aging is characteristic of these populations. Arterial premature aging is heterogeneous. It principally involves the aorta and central capacitive arteries, and is characterized by preferential aortic stiffening and disappearance of stiffness/impedance gradients between the central and peripheral arteries. These changes have a double impact: on the heart, upstream, with left ventricular hypertrophy and decreased coronary perfusion; and, downstream, on renal and brain microcirculation (decrease in glomerular filtration and cognitive functions). Multifactorial at origin, the pathophysiology of aortic ‘progeria' and microvascular disorders in CKD/ESRD is not well understood and should be the focus of interest in future studies.